1999
DOI: 10.1002/(sici)1097-0274(199901)35:1<43::aid-ajim6>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent occupational injuries: Texas, 1990-1996

Abstract: Background A comprehensive surveillance system for occupational injuries to adolescents does not exist in Texas, as in most states. Therefore, the magnitude, severity, nature, and source of injuries to working adolescents have not been well described in Texas. Methods The investigators used three data sources to investigate work‐related injuries and deaths in Texas: (1) Texas Workers' Compensation Commission (TWCC) claims data from 1991 through April 1996; (2) 1993 TWCC/Bureau of Labor Statistics (BLS) Annual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 18 publications
4
36
0
1
Order By: Relevance
“…Castillo et al (18) reported U.S. fatality rates for males (aged 16-17) of 8.49/100,000 full-time equivalents, compared with 0.91/100,000 for females. Two studies (27,31) report that >70% of the deaths among working adolescent females are homicides, a proportion that is considerably larger than the 41% homicide rate reported for all U.S. women from 1980-1985 (7).…”
Section: Gender and Racementioning
confidence: 99%
See 2 more Smart Citations
“…Castillo et al (18) reported U.S. fatality rates for males (aged 16-17) of 8.49/100,000 full-time equivalents, compared with 0.91/100,000 for females. Two studies (27,31) report that >70% of the deaths among working adolescent females are homicides, a proportion that is considerably larger than the 41% homicide rate reported for all U.S. women from 1980-1985 (7).…”
Section: Gender and Racementioning
confidence: 99%
“…Several studies of fatal youth injuries have been published in the last decade (18,19,27,28,30,31,65,68,75,82). Castillo et al (18) examined data from the National Traumatic Occupational Fatality System (NTOF), that documented fatalities recorded on death certificates as "injury at work" for U.S. workers aged 16 and 17 years.…”
Section: Fatalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, back pain in particular is of concern in adolescence, and may place these young workers at greater risk for future musculoskeletal problems. Risks of severe and even fatal injuries occur most frequently among boys rather than girls, 2,3,5,6,10,18 indicating different types of employment activities and possibly job demands. 6,18 In this study, data regarding fatal injuries were not collected.…”
Section: Discussionmentioning
confidence: 99%
“…8 Quantitative studies* performed in several countries show that work injuries are common among adolescents. [9][10][11]18 Azambuja 3 and Mangas* performed similar studies to assess the perception of work injuries among adults.…”
Section: Introductionmentioning
confidence: 99%